MOTHERS' PERCEPTIONS OF NEIGHBORHOOD DISORDER ARE ASSOCIATED WITH CHILDREN'S HOME ENVIRONMENT QUALITY. Issue 6 (August 2016) - Lin, Joyce; Reich, Stephanie M.
Abstract : This study examines how low–income mothers' perceptions of their neighborhoods are associated with the home environments they provide for their young children. The connection between neighborhoods and homes is important since they are nested systems that are critical to children's healthy development. Women's perception of their neighborhoods may affect the way they set up their homes and interact with their young children. Given that various women may perceive the same neighborhood differently, this study uses subjective, rather than typical objective measures of neighborhood disadvantage. After controlling for maternal background characteristics, including stress and depression, these data find that the more women perceive their neighborhood to be disordered, the less likely they are to provide high–quality home environments and be responsive to their infants. Establishing a link between neighborhood and home environments is important and illuminates avenues for potentially improving the contexts of young children's lives.